Strongly Participatory Science and Knowledge Justice in an Environmentally Contested Region. (November 2018) - Allen, Barbara L.
This article draws insights from a case study examining unanswered health questions of residents in two polluted towns in an industrial region in southern France. A participatory health study, as conducted by the author, is presented as a way to address undone science by providing the residents with relevant data supporting their illness claims. Local residents were included in the health survey process, from the formulation of the questions to the final data analysis. Through this strongly participatory science (SPS) process, the townspeople offered many creative ideas in the final report for how the data could be used to assist in improving their health and environment and policy work is already in evidence, resulting from the study. Drawing from the literature on participatory science and expertise as well as from the initial outcomes of the local health study, I propose that SPS produces a form of knowledge justice. Understanding knowledge and its making as part of a social justice agenda aligns well with environmental justice frames. Through SPS, local residents have a hermeneutical resource to make sense of their embodied lives and augment their claims with strong data supporting actions for improving their health and environment.